Coffee Growing in the Florida Home Landscape - Jonathan H. Crane; Carlos F. Balerdi; Gene Joyner (EDIS)
Revised! HS-1056, a 6-page fact sheet by Jonathan H. Crane, Carlos F. Balerdi, and Gene Joyner, provides homeowners with a basic reference for growing coffee in the home landscape. Tables include suggested cultural practices by month and nutritional values. Published by the UF Department of Horticultural Sciences, October 2006.